25. EFFECT OF STEREOTACTIC RADIOSURGERY COMPARED TO WHOLE-BRAIN RADIOTHERAPY FOR LIMITED BRAIN METASTASIS ON LONG TERM COGNITION AND QUALITY OF LIFE: A POOLED ANALYSIS OF NCCTG N107C/CEC.3 AND N0574 (ALLIANCE) RANDOMIZED CLINICAL TRIALS. (4th August 2020) - Palmer, Joshua; Klamer, Brett; Ballman, Karla; Brown, Paul; Cerhan, Jane; Anderson, Keith; Whitton, Anthony; Greenspoon, Jeffrey; Chung, Caroline; Burri, Stuart; Parney, Ian; Stieber, Volker; et al.
Abstract: PURPOSE: We investigated the long term impact of SRS and WBRT in two large prospective phase III trials. METHODS: Patients with 1–4 BMs +/- resection were randomized to SRS or WBRT. Cognitive deterioration was a drop of >1 standard deviation from baseline in >2/6 cognitive measures (CM). Quality of life (QOL) scores were scored 0–100 point scale. CM and QOL scores were modeled using baseline adjusted Linear Mixed Models (LMM) with uncorrelated random intercept for subject and random slopes for time. Differences in trend over time between groups and the effect of >2 cognitive scores with >2 SD change from baseline were assessed. RESULTS: 88 patients were included with median follow up of 24 months. We observed decreasing CM over time (SRS: 4/6; WBRT: 5/6). Mean CM was significantly higher in SRS for Total recall and Delayed Recall at 3, 6, 9, 12 months. More patients in WBRT arm declined 1 SD in >1 and >2 CM at the 3, 6, 9, and 12 months. A 1 SD decline in >3 CM at 1 year was 21% SRS vs 47% WBRT (p=0.02). SRS had fewer patients with a 2 SD decline in >1 CM at every time point. SRS had fewer patients with a 2 SD decline at >2 and >3 CM. WBRT had lower QOL at 3 months, but switched to SRS having lower QOL at 24 months for PWB, EWB, FWB, FactG, BR, and FactBR (p<0.05). A 2 SD decline in cognition decreased mean FWB by 6.4 units (95% CI: -11, -1.75; p=0.007) and decreased QOL by 5.1 units (95% CI: -7.7, -2.5; p<0.001). CONCLUSIONS: We report the first pooled prospective study demonstrating the long term outcomes of patients with BMs after cranial radiation. WBRT was associated with worse cognitive outcomes. Impaired cognition is associated with worse QOL.